Penggunaan Abu Sekam Padi Sebagai Bahan Pengisi (Filler) Dalam Campuran Aspal Jenis AC-WC Dengan Pengujian Marshall - Nopriwanda Syahputra; Alfian Malik; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In a pavement mixture, filler has a significant effect because its functions as a cavity filler in the mixture. The fillers commonly used are Portland cement, stone ash or fly ash which are relatively expensive. Therefore it is necessary to use alternative filler removal materials but not reduce the quality of the pavement mixture. In this study, the filler used was waste burning rice husk ash because it has a high silica content which is almost the same as Portland cement. The purpose of this study was to determine the effect of using rice husk ash filler in a mixture of AC-WC asphalt types. In this study the optimum asphalt content determination was carried out at asphalt levels 5%, 5.5%, 6%, 6.5% and 7%. The proportion of rice husk ash used were 0%, 2%, 4%, 6% and 8%. The specifications used follow the Bina Marga 2010 Revision 3 standard with the Marshall method. The results of this study indicate that the AC-WC mixture using rice husk ash filler has better stability than not using rice husk ash filler. The highest stability value is found at 6% filler level which is equal to 1701.00 kg. The recommended level of rice husk ash for AC-WC mixture that is according to specifications is 6% because it has a better value of stability, flow, VIM, VMA, VFA, MQ.Keywords: Rice husk ash, Filler, AC-WC, Bina Marga Specification 2010 Revision 3